Mathematical problem-solving ability: The effect of numbered head together (NHT) model and mathematical prior knowledge - Rany Widyastuti (CV. FOUNDAE, 2021)
This study aimed to determine the effect of the NHT (Numbered Head Together) cooperative learning model on mathematical problem-solving abilities in terms of students' mathematical prior knowledge. The researchers employed quasi-experimental research and collected the mathematical problem-solving data using a description test. At the same time, the researchers investigated students’ mathematical prior knowledge using the mid-semester examination (UTS) scores. The hypothesis was tested using the two-way ANOVA with unequal cells. The results showed that the NHT learning model provided better problem-solving skills than the direct learning model. The category of students' prior knowledge also affected their mathematical problem-solving abilities. Therefore, teachers should pay attention to the prior knowledge possessed by students so that an appropriate learning model can be selected.